Eastern direction in Rzeczpospolita’s foreign policy - Komar, Volodymyr (Skhid, 2013)
The article deals with formation of Poland’s eastern policy during the Middle Ages, the aim of which was to join the Ukrainian, Lithuanian, and Byelorussian lands.